Impact of Subcontracting and Outsourced Processes on Effective Project Management - Shirvani, Ramin (2012)
The purpose of this is to see the importance to see risk management as a whole, in any industry, in any field. Whether looking at an industry such as the banking industry of RBS/NatWest or automobile industry such as Toyota or the aviation industry such as Boeing. There are common occurrences between these industries; however these companies and their decisions will differ. Is one better than the other, in how they manage risk; is there one correct way to manage risk; these questions are not what I will develop in the end, but more of a comparative analysis of these companies, as no two companies are the same, and it is important to stress that. In this paper, I have highlighted various authors on shown how they agree on the incomplete areas of project management. This paper discusses what a project must consist of to become either successful or a failure. It is essential that a project from the initiation stage have all the contractual ideals on what makes a project become successful or a failure, even if the project manager brings in the project on time, under budget and within quality specifications. Outsourcing of project activities is a normal occurrence, across all sectors of industries. This paper takes a look at  Lloyds TSB  RBS/NatWest  The Boeing Company  Virgin Australia  Toyota  Avis Europe, Middle East, Africa and Asia (AEMEAA)  Coca-Cola This paper will show what happens when projects are outsourced, that the need for organizations to make sure they make project management aligned to the internal needs of the organization rather than just being customer-driven. The analysis shows that even when RBS/NatWest had a major service update fail on June of 2012, that was outsourced, 119 customers surveyed, with a ±10% margin of error, 72.9% of respondents said that outsourcing was not important to their buying decision, while 24.4% were unsure and 2.5% said that it was important. As 35.6% of respondents said that they were neither pleased nor displeased with their NatWest service, but what this graph also shows, is that 48.3%